Evolutionary and neuropsychological perspectives on addictive behaviors and addictive substances: relevance to the "food addiction" construct - Davis C (Dove Medical Press, 2014)
Caroline Davis School of Kinesiology and Health Science, York University, Toronto, ON, Canada Abstract: It has been argued that food cannot be "addictive", unlike conventional drugs of abuse, because it is an essential part of life. In this paper, evidence is reviewed, largely from an evolutionary psychobiological perspective, that plant-based psychoactive drugs (such as those derived from the opium poppy and the coca leaf) and gambling-related behaviors were once adaptive for human health and survival in a similar manner as energy-based foods were for nourishment. "Evolutionary mismatch" viewpoints contend that certain behaviors were enhanced during the hunter-gatherer lifestyle – from which our genetic endowment had its origins – because they bestowed both survival and reproductive advantages to the species. However, in the context of advanced technology and other rapid environmental changes, these same behaviors have tended to become maladaptive and greatly overexpressed. Similar to the manufactured purification of psychotropic plant-based substances, the reward impact of processed and hyperpalatable foods, with their high levels of sugar, fat, and salt, is much increased from foods produced in nature. It is concluded therefore that what was once beneficial and necessary for our survival has been altered and ultraprocessed into edible products that may be disadvantageous and potentially addictive. Keywords: food addiction, evolution, drugs, gambling